Adult-type non-rhabdomyosarcoma soft tissue sarcomas in pediatric age: Salvage rates and prognostic factors after relapse. (July 2022) - Chiaravalli, Stefano; Bergamaschi, Luca; Livellara, Virginia; Sironi, Giovanna; Puma, Nadia; Nigro, Olga; Gattuso, Giovanna; Luksch, Roberto; Terenziani, Monica; Spreafico, Filippo; Meazza, Cristina; Podda, Marta; et al.
Abstract: Purpose: Though the prognosis for patients with pediatric non-rhabdomyosarcoma soft tissue sarcomas (NRSTS) is generally good, the chances of being cured after relapse are limited. This report describes a series of relapsing NRSTS patients treated at a referral center for pediatric sarcoma, investigating the pattern of relapse, salvage rates, and factors correlating with the final outcome. Methods: The analysis concerned 103 patients <21 years old with relapsing adult-type NRSTS treated from 1985 to 2020. For risk-adapted stratification purposes, the patient outcome was examined using univariable and multivariable analyses based on patients' clinical features at first diagnosis, first-line treatments, clinical findings at first relapse, and second-line treatments. Results: The first relapse occurred within 2–102 months (median 14 months) after patients' first diagnosis and was local in 47%, metastatic in 34%, and both in 19%. Treatment at relapse included chemotherapy in 72 patients, radiotherapy in 38, and surgery in 55. The median overall survival (OS) was 20 months. Post-relapse OS was 56.1%, 25.8%, and 19.1% at 1, 5, and 10 years, respectively. Cox's multivariable regression analysis showed that OS was significantly better for patients with local and late relapses (occurring more than 12 months after their first diagnosis) and for those achieving secondary remission. Conclusion: The outcome of patients with recurrent NRSTS is poor. The above-mentioned variables (type and time of relapse and achievement of secondary remission) were combined in a risk-adapted model to develop a tool for estimating the chance of salvage and deciding the best second-line treatment approach. Highlights: Pediatric non-rhabdomyosarcoma soft tissue sarcomas (NRSTS) are heterogeneous. The chances of being cured for NRSTS patients who relapsed are limited. In the series, median post-relapse survival was 20 months, 10-year survival was 19.1%. Survivals were better after local and late relapses and after secondary remission. Prognostic factors were combined in a risk-adapted model.